2019
DOI: 10.7185/geochemlet.1904
|View full text |Cite
|
Sign up to set email alerts
|

Radiogenic Ca isotopes confirm post-formation K depletion of lower crust

Abstract: Heat flow studies suggest that the lower crust has low concentrations of heat-producing elements. This could be due to either (i) greater fractions of basaltic rock at depth or (ii) metamorphic depletion of radioactive elements from rocks with more evolved (andesitic to granodioritic) compositions. However, seismic data suggest that lower crust is not predominantly basaltic, and previous studies (using Pb and Sr isotopes) have shown that lower crustal rocks have experienced significant losses of U and Rb. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…We only report data where absolute measurement uncertainties on 40 Ca/ 44 Ca were ≤0.003 (2SE), which are typically (but not always) achieved in a standard measurement (Figure S1a). Three of the 42 samples included in our compilation (Figure 2) from Antonelli et al (2019) 25 have uncertainties larger than this (Supplementary Data Table 3). Taking into account the fractionation extents on the filaments, only 2 out of 79 analyses from the current study have fractionations beyond the value (−2‰ amu −1 ) suggested for high quality data by Caro et al ( 2010) 16 (Figure S1a, Supplementary Data Table 3).…”
Section: ■ Materials and Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…We only report data where absolute measurement uncertainties on 40 Ca/ 44 Ca were ≤0.003 (2SE), which are typically (but not always) achieved in a standard measurement (Figure S1a). Three of the 42 samples included in our compilation (Figure 2) from Antonelli et al (2019) 25 have uncertainties larger than this (Supplementary Data Table 3). Taking into account the fractionation extents on the filaments, only 2 out of 79 analyses from the current study have fractionations beyond the value (−2‰ amu −1 ) suggested for high quality data by Caro et al ( 2010) 16 (Figure S1a, Supplementary Data Table 3).…”
Section: ■ Materials and Methodsmentioning
confidence: 89%
“…For most samples, Ca was separated from matrix elements using established column chemistry methods (DGA resin, 3 M HNO 3 , and ultrapure water), which are the same as used in . 25 Briefly, powdered silicate samples were dissolved in 2:1 mixtures of concentrated HF and 6 M HCl, refluxed for at least 1 week at 120 °C, evaporated and then redissolved in 3 M HNO 3 and refluxed at 120 °C for several days to ensure complete dissolution of the samples with no visible residue. Carbonate samples were first dissolved in 6 M HCl, placed on a hot plate at 120 °C for >24 h, evaporated, and redissolved in 3 M HNO 3 for column chemistry.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Moreover, the potassic to ultrapotassic composition of the analysed anatectic melts may indicate that crustal anatexis can have a larger impact in the redistribution of heat‐producing elements (such as K 2 O), with important implications for the thermal structure of the continental crust (e.g. Antonelli, DePaolo, Chacko, Grew, & Rubatto, 2019; Hacker et al., 2015). This study shows that anatectic MI provide a fundamental insight into the comprehension of the melting regime in UHT terranes and the chemical differentiation of the lower crust.…”
Section: Discussionmentioning
confidence: 99%
“…To allow for easier comparison with published data and to best illustrate complementarity between terrestrial reservoirs, δ 44/42 Ca values are converted to δ 44 Ca by multiplying by 2.05 (the kinetic mass law) and are reported relative to BSE [with a recommended value of +0.95‰ relative to SRM915a 14 , which is +0.25‰ relative to SRM915b in this study]. As 40 Ca is not directly measured, the use of MC-ICP-MS for stable Ca isotope analyses precludes the need for radiogenic 40 Ca corrections, which could otherwise lead to significant variations in Archean-aged samples analyzed by thermal-ionization mass spectrometry 35 , 36 , 40 .…”
Section: Methodsmentioning
confidence: 97%
“…Calcium (~50 μg) is separated from aliquots of the dissolved samples and standards using established column chemistry methods adapted from UC-Berkeley 21 , 35 38 and modified for multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS) analyses 39 . Eichrom ® DGA resin is thoroughly washed by alternating between ultrapure water and 4 M HNO 3 several times overnight before loading into home-made Teflon columns with ~2 mL reservoirs.…”
Section: Methodsmentioning
confidence: 99%